Investigation of Mo:Na and Mo related back contacts for the application in Cu(In, Ga)Se2 thin film solar cells. (July 2019) - Zhu, H.; Dong, Z.; Pan, L.; Han, Q.; Niu, X.; Li, J.; Shen, K.; Mai, Y.; Li, Y.; Wan, M.
Highlights: Mo:Na thin films are deposited by DC and RF sputtering at different working pressures. Mo:Na thin films are employed as back contact in CIGS thin film solar cells. The incorporation of Na into CIGS thin films would increase the VOC of the solar cells. Abstract: In this study, sodium doped molybdenum (Mo:Na) and Mo thin films are deposited at different working pressures under the excitation of the radio frequency (RF) or direct current (DC) power supplies for application in Cu(In, Ga)Se2 (CIGS) thin film solar cells. The various material properties including dynamic deposition rate, electrical and optical properties, crystal structure and morphology are systematically investigated and compared for these RF and DC sputtered Mo:Na and Mo thin films. Mo and Mo:Na related back contacts, i.e. bottom Mo:Na layer prepared at a high working pressure and top Mo or Mo:Na thin film sputtered at a low working pressure are employed in CIGS thin film solar cells. CIGS thin film solar cells with Mo:Na (bottom, DC)/Mo:Na (top, DC) have a relatively high VOC, which is related to a relatively easy migration of Na passing through the DC Mo layers and entering into the CIGS thin film solar cells. A CIGS thin film solar cell of 14.0% has been achieved in this work.